Atrial Arrhythmia Ablation in Patients With D-Transposition of the Great Arteries and Atrial Switch. (28th June 2022) - Chiriac, Anca; Cheema, Kamal P.; Giardi, Davide; Espinosa, Samantha M.; Fitzgerald, Patrick; Perez-Downes, Julio C.; Umadat, Goyal; Hodge, David O.; Phillips, Sabrina D.; Madhavan, Malini; Asirvatham, Samuel J.; McLeod, Christopher J.
Abstract : Background: Patients with D-transposition of the great arteries and atrial switch have a high incidence of atrial arrhythmias. We sought to analyze the arrhythmia substrate, ablation strategies, and outcomes for catheter ablation in this population. Methods: An in-depth analysis of all clinical and procedural data in patients with D-transposition of the great arteries, atrial baffles, and atrial arrhythmia ablation was performed. Results: A cohort of 32 patients (72% male, mean age 38±7 years) underwent ablation for non-AV nodal reentrant tachycardia atrial arrhythmias, and 4 patients underwent AV nodal reentrant tachycardia ablation. Cavotricuspid isthmus flutter (CTI-flutter) was the most common arrhythmia, encountered in 75% of patients, followed by scar-related intraatrial reentrant tachycardia (non-CTI intraatrial reentrant tachycardia, 53%) and focal atrial tachycardia (focal atrial tachycardia, 6%). Among the 32 patients, 26 underwent 31 procedures at our institution. For patients with prior outside intervention, the index ablation at our institution revealed CTI-dependent flutter in 3/5 cases. However, redo ablation after an index ablation with demonstrated bidirectional CTI block revealed different/new arrhythmia substrates (80% non-CTI intraatrial reentrant tachycardia, 40% focal atrial tachycardia). Achieving bidirectional block across the CTI often required ablating on both sides of the baffle (retroaortic access, 81%; using a baffle leak, 11.5%; or transbaffle puncture, 7.7%). Combined approaches were necessary in 19% to reach the critical tissue. Acute procedural success was 81%, and recurrence was documented in 58% of patients. Despite recurrence, clinical arrhythmia burden was significantly reduced post-ablation ( P <0.001), with rare episodes, amenable to antiarrhythmic therapy. Redo ablation was required in 5 (19%) patients and uncovered new arrhythmia substrates. AV nodal reentrant tachycardia ablation also required transbaffle approaches in 3/4 patients. Conclusions: CTI-dependent flutter was the most common arrhythmia in patients with Dextro-Transposition of the Great Arteries and atrial switch. Transbaffle approaches were often necessary, and, provided that bidirectional CTI block was achieved at the index ablation, late recurrence was due to different arrhythmia mechanisms. Despite recurrence, ablation was associated with significant clinical improvement.